Computer aided semen analysis (CASA) to determine the quality and fertility of frozen thawed sumba ongole sperm supplemented with amino acids - Tulus Maulana; Paskah Partogi Agung; Muhammad Gunawan; Syahruddin Said (Livestock and Animal Research, 2022)
Objective: The objective of this research was to investigate the quality and reproductive potential of frozen-thawed Sumba Ongole (SO) bull spermatozoa supplemented with specified amino acids using computer-assisted semen analysis (CASA).Methods: A total of 18 ejaculates were collected once a week from three Sumba Ongole bulls and diluted in tris-citric-fructose-egg yolk (TCFY) extender and various concentrations of selected amino acids. The post-thaw spermatozoa were examined for motility, head behavior, and swimming pattern using CASA technique.  Data were analysis using SPSS 24 ebvaluated by ANOVA.Results: Total motility (72.56%±3.20) and progressive motility (71.11%±3.31) the addition of Glutamine 5% significantly different (p<0.05) than other treatments. The addition of 7mM cysteine resulted in significantly (p<0.05) in velocity average path (VAP), velocity curve line (VCL), velocity straight line(VSL) parameters also have higher in distance average path (DAP), distance curve line (DCL), dan distance straight line (DSL) parameters significantly (p<0,05).  Conclusion: In conclusion, the introduction of CASA systems enabled quantification of individual spermatozoa motility patterns and CASA colud be used to estimate the fertilizing capacity of sperm based on the characteristics of sperm velocity.